Structure and Menthone Encapsulation of Corn Starch Modified by Octenyl Succinic Anhydride and Enzymatic Treatment - Xuan Ji; Jing Du; Jiaying Gu; Jie Yang; Li Cheng; Zhaofeng Li; Caiming Li; Yan Hong (Journal of Food Quality)
In order to improve the ability of starch to absorb menthone, corn starch was modified by enzymatic treatment (amyloglucosidase and α-amylase) combined with octenyl succinic anhydride (OSA) esterification. The oil absorption rate of starch modified by enzymatic treatment followed by OSA (P-OSA) reached 101.33%, whereas that of samples with reverse action sequences (OSA-P) was only 59.67%. The degree of substitution of OSA-P was also generally lower than that of P-OSA. At high OSA addition, OSA-P had a smaller specific surface area with fewer pores because octenyl succinic (OS) groups impeded the enzymatic treatment. Compared with OSA-P, the lamellar structure of P-OSA is sparser and less ordered. Owing to its pores, P-OSA was beneficial for the reaction to occur inside the granules, which was observed by Raman spectroscopy and laser confocal microscopy. At high OSA addition, the loading of P-OSA to menthone could reach 64.34 mg/g.